2007
DOI: 10.1159/000107511
|View full text |Cite
|
Sign up to set email alerts
|

GPR54 Polymorphisms in Chinese Girls with Central Precocious Puberty

Abstract: Aims: The GPR54 gene has been proved to be important in the process of puberty onset, yet no association study has been performed to evaluate the effect of polymorphisms in the gene on central precocious puberty (CPP). This study was designed to scan for polymorphisms in the GPR54 gene and to investigate the relationships between the genotypes of GPR54 and the disease. Methods: 272 Chinese Han girls diagnosed to be CPP patients were recruited as the case group and 288 unrelated normal Chinese Han girls as the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
35
0
4

Year Published

2008
2008
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(40 citation statements)
references
References 30 publications
1
35
0
4
Order By: Relevance
“…Activated mutations of KISS-1 and GPR54 genes had been shown to cause central precocious puberty resulting from early maturation of the hypothalamicpituitary-gonadal axis in human (14)(15)(16). The present study preliminarily showed an association between alleles B and D of GPR54 gene and sexual precocity and high litter size in Jining Grey goats.…”
supporting
confidence: 63%
“…Activated mutations of KISS-1 and GPR54 genes had been shown to cause central precocious puberty resulting from early maturation of the hypothalamicpituitary-gonadal axis in human (14)(15)(16). The present study preliminarily showed an association between alleles B and D of GPR54 gene and sexual precocity and high litter size in Jining Grey goats.…”
supporting
confidence: 63%
“…The A/G coding sequence SNP on the GPR54 (KISS1R) gene (dbSNP ID: rs10407968) was previously identified by others [22,33] in a population of male patients with idiopathic hypogonadotropic hypogonadism, but no association with this disorder was found. Moreover, this polymorphism has not been recorded in a large population of Chinese girls (24 girls randomly selected from 272 girls with ICPP vs. 288 unrelated normal girls) who were screened for GPR54 (KISS1R)'s SNPs through direct sequencing [34]. The discordance in these data between Chinese and Caucasian populations cannot be explained by a different frequency of rs10407968 polymorphism in the Chinese general population, since it is reported to be 13.3% for G allele and therefore it is not represented significantly lower than the 15.7% representing the frequency of this allele in the Caucasian population (χ 2 test, p = 0.3).…”
Section: Discussionmentioning
confidence: 99%
“…A KISS1R mutation (Pro196His) located in the second extracellular loop of the receptor was identified (49), as was a kisspeptin variant (Pro110Thr). No functional studies have been performed for either mutation, so the mechanism by which these mutations might be associated with precocious puberty remains to be elucidated (49,50).…”
Section: Figmentioning
confidence: 99%